Landscape scale control of selected mammalian predators fails to protect lizards - Joanne M. Monks; Anne A. Besson; Colin F. J. O’Donnell (Biological Invasions, 2024)
Invasive mammalian predators are a global biodiversity problem, particularly in archipelagos in which native fauna evolved in isolation from mammals. Landscape scale management of selected invasive mammalian predators is occurring across Aotearoa New Zealand to protect vulnerable forest birds and bats. In temperate southern beech forests, both predator irruptions and the timing of predator control is driven by mast seeding of beech trees. Relationships between predators targeted in this control, other invasive mammalian predators and other native taxa, particularly lizards and invertebrates, are poorly understood. We monitored southern grass skinks in the Eglinton Valley, Fiordland from 2009 to 2020 alongside monitoring of predators (stoats, rats and mice) in a system where predator control occurred in response to mast seeding. We evaluated relationships between skink abundance and abundance of rats (targeted in predator control operations) and mice (which also prey on small vertebrates like lizards, but are not controlled). Skink abundance declined over time and was negatively correlated with mouse abundance, but not correlated with rat abundance. Current landscape predator control to protect forest birds and bats is likely insufficient to protect ground-dwelling lizards, and may actually be detrimental to lizard populations if controlling the other predators contributes to a mesopredator release of mice. Mice are significant predators of a range of small vertebrates and large invertebrates, yet research into the sustainable suppression of mice to benefit vulnerable native populations is lacking. We strongly advocate for such research in order to deliver conservation management that benefits the full suite of biodiversity.